Post‐weaning parental care increases fitness but is not heritable in North American red squirrels. (25th May 2015) - Lane, J. E.; McAdam, A. G.; Charmantier, A.; Humphries, M. M.; Coltman, D. W.; Fletcher, Q.; Gorrell, J. C.; Boutin, S.
Abstract Most empirical attempts to explain the evolution of parental care have focused on its costs and benefits (i.e. fitness consequences). In contrast, few investigations have been made of the other necessary prerequisite for evolutionary change, inheritance. Here, we examine the fitness consequences and heritability (h2) of a post‐weaning parental care behaviour (territory bequeathal) in a wild population of North American red squirrels. Each year, a subset (average across all years = 19%) of reproductive females bequeathed their territory to a dependent offspring. Bequeathing females experienced higher annual reproductive success and did not suffer a survival cost to themselves relative to those females retaining their territory. Bequeathing females thus realized higher relative annual fitness [ω = 1.18 ± 0.03 (SE)] than nonbequeathing females [ω = 0.96 ± 0.02 (SE)]. Additive genetic influences on bequeathal behaviour, however, were not significantly different from 0 (h2 = 1.9 × 10−3; 95% highest posterior density interval = 3.04 × 10−8 to 0.37) and, in fact, bequeathal behaviour was not significantly repeatable (R = 2.0 × 10−3; 95% HPD interval =0–0.27). In contrast, directional environmental influences were apparent. Females were more likely to bequeath in years following low food abundance and when food availability in the upcoming autumn was high. Despite an evident fitness benefit, a lack of heritable genetic variance will constrain evolution of this trait.